2020
DOI: 10.12659/msm.924934
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis and Identification of Underlying Biomarkers Potentially Linking Allergic Rhinitis and Asthma

Abstract: Background:Rhinitis is the most common clinical manifestation of allergy, affecting more than 400 million people around the world. Rhinitis increases the risk of developing bronchial hyper-responsiveness and asthma. Previous studies have shown that rhinitis is closely related with the physiology, pathology, and pathogenesis of asthma. We analyzed co-expressed genes to explore the relationships between rhinitis and asthma and to find biomarkers of comorbid rhinitis and asthma. Material/Methods:Asthma-and rhinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 49 publications
2
21
0
1
Order By: Relevance
“…Although more research is needed, the proteolytical cleavage of endothelin-1 and other known CPA3 targets, such as neurotensin, angiotensin-1 and apolipoprotein B, further implies potentially broad roles of CPA3 in vascular homeostasis. Naturally, despite its potential role in protection and homeostasis, CPA3 mRNA is upregulated in many diseases [ 11 , 13 , 26 , 42 , 43 ] and may also have more pro-inflammatory or pathogenic actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although more research is needed, the proteolytical cleavage of endothelin-1 and other known CPA3 targets, such as neurotensin, angiotensin-1 and apolipoprotein B, further implies potentially broad roles of CPA3 in vascular homeostasis. Naturally, despite its potential role in protection and homeostasis, CPA3 mRNA is upregulated in many diseases [ 11 , 13 , 26 , 42 , 43 ] and may also have more pro-inflammatory or pathogenic actions.…”
Section: Discussionmentioning
confidence: 99%
“…However, mast cell granules contain other less explored proteases, which are likely to have significant biological roles, such as cathepsin G, renin, MMP9, active caspase 3, and carboxypeptidase A3 (CPA3) [ 4 ]. Interestingly, CPA3 has recently been highlighted in multiple gene signature studies where CPA3 expression has been linked to eosinophilic esophagitis [ 8 , 9 ], colon cancer [ 10 ], and eosinophilic type 2 asthma [ 11 , 12 , 13 ]. Although these observations indicate clinically important roles for CPA3, there is limited information regarding its substrate cleavage profile.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Furthermore, miR-21 and miR-125a, as the targets of lncRNA NEAT1 via a ceRNA regulatory network, are shown to participate in the pathological process and present potential to be biomarkers of allergic inflammation diseases. [ 10 , 16 , 21 ] For example, miR-125a is downregulated and negatively correlates with disease risk, inflammation and disease severity of bronchial asthma. [ 22 ] Additionally, one study reveals that decreased miR-21 expression is correlated with elevated lgE production in neonatal leucocytes, promoting development of AR.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Zhanfeng Yan et al discussed the coexpressed DEGs of CST1 and CPA3 and found that there were significant correlations of the CST1 and CPA3 genes with novel biomarkers involved in the comorbidity of rhinitis and asthma. [24] In addition, Natasha A Winter et al found that the gene expression of TPSAB1/TPSB2 and CPA3 correlated with sputum mast cells/basophils, and in severe asthma, TPSB2 and CPA3 were associated with eosinophilic airway inflammation and blood eosinophils. [25] The hub gene ITLN1, which is expressed in airway epithelial cells and involved in inflammatory pathways downstream of IL-13, was found to be significantly upregulated in the bronchial brushings of patients with asthma compared with controls.…”
Section: Discussionmentioning
confidence: 99%